Penerapan Dimensi Sound Governance dalam Pelayanan Publik di Kantor Samsat Kabupaten Gowa - Rahmat Hidayat; Muhlis Madani; Rudi Hardi (Department of Public Administration, Muhammadiyah University of Makassar, 2015)
The aim of this research is to find out the Application of Sound Governance on the public service in the SAMSAT Office, Gowa. In addition, to determine the public perception of the services in SAMSAT office by linking with a Sound Governance. The study was phenomenological type. The research method is descriptive qualitative that the researcher intends to give a description or explanation about the implementation of Sound Governance on the public service in the SAMSAT office. The result of this research indicated that the implementation of sound governance dimension on the public service at the SAMSAT office, Gowa. It was about the process of decision-making, policy and implementation which is be better. The structural or regulatory rules and actors in the public service had been running optimally. Management and performance on the sound governance dimention in the public service in the SAMSAT Office had been TUPOKSI very well. The public perception on the service in the SAMSAT Office with regard to sound governance, namely: (a) the transparency on the public service in the SAMSAT office Gowa was still minimal, so only the partially which they publish to the public; (b) Conditional on the public service in the SAMSAT office Gowa still need to be in good order. So that the conflict between employes with the community can be minimized; (C) Equal rights on the public service in the SAMSAT office, Gowa.. There are still differences in terms of services. Keywords: dimensional sound governance, public services Tujuan Penelitian yaitu untuk mengetahui Penerapan Sound Governance dalam pelayanan publik di Kantor SAMSAT Kabupaten Gowa, selain itu untuk mengetahui Persepsi Publik terhadap pelayanan di Kantor SAMSAT dengan mengkaitkan dengan Sound Governance. Tipe Penelitian bersifat fenomenologis. Jenis penelitian yang dilakukan adalah deskritif kualitatif yaitu penulis bermaksud untuk memberikan gambaran atau penjelasan mengenai Penerapan Sound Governance dalam pelayanan publik di Kantor SAMSAT Kabupaten Gowa. Hasil Penelitian ini menunjukkan bahwa penerapan dimensi sound governance dalam pelayanan publik di kantor SAMSAT Kabupaten Gowa adalah mengenai proses dalam pengambilan keputusan, kebijakan dan pelaksanaanya sudah cukup baik. Struktural yang di sini Aturan atau regulasi dan aktor dalam pelayanan publik sudah berjalan dengan optimal. Manajemen dan kinerja dalam dimensi sound governance pelayanan publik di Kantor SAMSAT sudah menjalankan TUPOKSI dengan baik. Persepsi publik terhadap pelayanan di Kantor SAMSAT dengan kaitannya dengan sound governance yaitu: (a) Transparansi dalam pelayanan publik di kantor SAMSAT Kabupaten Gowa, masih minim sehingga hanya sebagian saja yang mereka publikasikan ke masyarakat; (b) Kondisional dalam pelayanan publik di Kantor SAMSAT Kabupaten Gowa masih perlu di tata dengan baik sehingga pertentangan antara pengawai dengan masyarakat dapat diminimalisir; (c) Kesamaan Hak dalam pelayanan publik di Kantor SAMSAT Kabupaten Gowa disini masih ada perbedaan dalam hal pemberian pelayanan. Kata kunci: dimensi sound governance, pelayanan publik